Rehabilitation Program for Transverse Myelitis - John Hartono; Tanti Ajoe Kesoema; Robby Tjandra Kartadinata (Indonesian Journal of Physical Medicine & Rehabilitation, 2019)
Introduction: Transverse myelitis is a neurological disease involving inflammation or lesions on the spinal cord with rapid and progressive onset of symptomsMotor training, sensory stimulation, andrehabilitation of autonomic functions are needed, to restore the function, reduce disability, and improve the quality of life.Case Presentation: A 34 years old male had weakness and loss of sensoric of lower limbs, accompanied by low back pain (LBP), chronic cough, and micturition dysfunction for 1 month ago, categorized byASIA impairment scale (AIS) D, level of injury at T6. The MRI of Thoracolumbal showed myelitis lession at 6th – 7th of thoracal, effusion at facet joint of L2-L5, and lumbal spondylosis. The rehabilitationprograms were active range of motion exercise with walking exercise (3 session/week, 30 minutes/session), Transcutaneous Electrical Nerve Stimulation (2-10 pps, 2 session/week, 20 minutes/session),sensory stimulation (2 session/week, 20 minute/session), and bladder training for 3 weeks. After 16 days, there were lower limb’s strength improvement by Manual Muscle Testing (MMT) were average four atlevel L2-S1, sensory improvement to T9-10, LBP was reduced, and normal micturition. After 3 weeks, lower limb strength improved to 55445/55445 at level L2-S1. Pat ient able to walk without assisted.Conclusion: Muscle strengthening, sensory simulation and bladder training, combined with pharmacological treatment, improved motor, sensory and autonomic function in Transverse MyelitispatientKeywords: Motoric training, sensory stimulation, bladder training, Transcutaneous electrical nerve stimulation, transverse myelitis